The efficacy of interviewing young drug users through online chat - Barratt, Monica (Informa Healthcare, 2012)
Introduction and Aims. Despite the fact that most young people who use ‘party drugs’ also use the Internet, accounts of drugs research involving qualitative interviewing using real-time instant messaging or online chat are yet to be published. This paper assesses the efficacy of conducting qualitative research interviews with young party drug users through instant messaging. Design and Methods. In 2007–2008, 837 Australian residents who reported recent use of psychostimulants and/or hallucinogens and participated in online drug discussion completed a web survey and a subsample of 27 completed online interviews (median age 21, range 17–37, 59% male). Results. Experienced drug users were more likely to volunteer to be interviewed than novices. The time and space flexibility provided by the online interviews was convenient; however, interviews were more prone to interruption. Establishing legitimacy, personal disclosure, appropriate linguistic style and humour facilitated the development of rapport and enabled the production of more detailed and in-depth data. These strategies were not successful in all cases and when unsuccessful, interviewees were more easily able to exit the interview by choosing not to respond. Discussion and Conclusions. Young drug users already using the Internet to chat about drugs find online interviewing an acceptable and convenient way to contribute to research. With adequate preparation to develop technical and cultural competencies, online interviewing offers an effective way of engaging with young people that is worthy of consideration by researchers in the alcohol and other drug field.